Effect of Anti-interleukin-17 Treatment on Haemoglobin A1c Levels - Christopher Willy Schwarz; Nikolai Dyrberg Loft; Claus Zachariae; Lone Skov (Medical Journals Sweden, 2020)
Abstract is missing (Short communication)